ANALISIS RESEPSI NILAI-NILAI BUDAYA PALESTINA MELALUI MEDIA DONGENG PADA SISWA SD AL-ZAHRA INDONESIA - Marsya Fadhia Akmal; Gugum Okta Riansyaha; Mulyani; Nuruddin; Miftahulkhairah Anwar (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This article aims to motivated by support for the world’s peace campaign by introducing foreign (Palestinian) cultural values which are full of value of the humanity and divinity. Besides that, their sacrifice and struggle are also worth learning. The main purpose of this research is to grow the feeling of loving people abroad since they are young. The other goal (as a synchronization with the main goal) is to train children to feel sympathy and empathy as well as the form of moral and material support for the Palestinian people who are still fighting for their independence. The focus or highlight of this research is to prove that literary works in the form of dongeng can be used as a medium in conveying cultural values. The method that the researcher uses in this research is the naturalistic-qualitative. Data was collected by various techniques such as; practicing the tale entitled